1985
DOI: 10.1039/p19850001349
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of reduction of the vitamin folic acid by dihydrofolate reductase

Abstract: Reduction of the vitamin folic acid (6) to the coenzyme 5,6,7,8-tetrahydrofolic acid ( I ) by the enzyme dihydrofolate reductase is shown to involve transfer of the 4-pro R hydrogen of NADPH to the same face at both C-6 and C-7 of the pteridine system (the re face at C-6 and the siface at C-7). The orientations of the pteridine system of folic acid (6) and of dihydrofolic acid (5) when bound to the enzyme are different from the orientation of the pteridine ring of the anti-cancer drug methotrexate (I I ) when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 4 publications
4
22
0
2
Order By: Relevance
“…43 On this basis, it is plausible that the pro-R rather than the pro-S (3.3 Å) hydrogen at C-4 of NADPH is transferred to the C-1′ position of DAROPP (Figure 10(c)), in analogy to the known stereospecificity of the DHFR reaction. 44 In contrast to riboflavin type reductases, the enzymatic mechanism of DHFR has been studied in more detail (Figure 10(a)). [45][46][47][48] The reaction occurs by hydride transfer of hydrogen 4 of NADPH to C-6 of H 2 F and protonation of N-5.…”
Section: Discussionmentioning
confidence: 99%
“…43 On this basis, it is plausible that the pro-R rather than the pro-S (3.3 Å) hydrogen at C-4 of NADPH is transferred to the C-1′ position of DAROPP (Figure 10(c)), in analogy to the known stereospecificity of the DHFR reaction. 44 In contrast to riboflavin type reductases, the enzymatic mechanism of DHFR has been studied in more detail (Figure 10(a)). [45][46][47][48] The reaction occurs by hydride transfer of hydrogen 4 of NADPH to C-6 of H 2 F and protonation of N-5.…”
Section: Discussionmentioning
confidence: 99%
“…16 An interesting observation from early studies on DHFR is that the pteridine moiety of MTX binds in the active site in an orientation different from that adopted by the substrate DHF. 31 Likewise, in PTR1, the substrates bind with the pteridine rotated about the N2-N5 axis by 1808 relative to MTX.…”
Section: Substrate and Product Complexesmentioning
confidence: 99%
“…For this, we prepared selectively deuterated 5,6,7,8- We then determined the sites of deuteration in the product by comparing the 1 H spectra of the deuterated and nondeuterated tetrahydrofolates. It could be shown that the deuterons which are transferred to the C6 and C7 positions are both added onto the same face of the pterin ring [41,42] (see structure 3). The absolute configuration of the hydrogen atom at the 6-position of tetrahydrofolate was already known to be 6S from earlier X-ray crystallographic studies.…”
Section: Insights Into the Mechanism Of Dihydrofolate Reductasementioning
confidence: 99%
“…In the X-ray structure of the complex of DHFR with methotrexate (5, MTX) and NADPH, [13,14] the ªtransfer-redº proton 4-H R of NADPH is located near the opposite face of the MTX pteridine ring to that which receives the protons in the folate reduction. [13, 14, 41±45] Thus, although methotrexate (5) and folate (1) have similar structures, differing only at positions C4 and N10, the pteridine ring of 5 binds to DHFR in a different orientation to that of 1 [41,42] and 7,8-dihydrofolate. [13,43,45] This behavior has been confirmed in subsequent X-ray [16] and NMR structural studies, [27,46] where the pterin ring in the DHFR ± folate complex was found to be turned over by about 1808 relative to its orientation in the DHFR ± MTX complex.…”
Section: Insights Into the Mechanism Of Dihydrofolate Reductasementioning
confidence: 99%